2001
DOI: 10.1542/peds.108.3.e57
|View full text |Cite
|
Sign up to set email alerts
|

Technical Report: Evidence for the Diagnosis and Treatment of Acute Uncomplicated Sinusitis in Children: A Systematic Overview

Abstract: ABSTRACT.Objective. To evaluate and analyze the existing evidence for the diagnosis and treatment of acute uncomplicated sinusitis in children.Design. A systematic overview and meta-analysis considered all pertinent studies with at least 10 children younger than 18 years with acute symptoms of <30 days and without serious complications.Outcomes. Clinical improvement rates for intervention studies of antibiotics or ancillary measures; concordance of diagnostic tests (expressed as likelihood ratios).Results. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 29 publications
0
24
0
1
Order By: Relevance
“…Previous systematic reviews have been limited by focusing only on children, 10,11 have not identified all relevant studies, 11 or are ≥10 years old. 10,12 The goal of the current study is to perform an updated, comprehensive systematic review of the accuracy of imaging and laboratory tests for the diagnosis of ARS and ABRS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous systematic reviews have been limited by focusing only on children, 10,11 have not identified all relevant studies, 11 or are ≥10 years old. 10,12 The goal of the current study is to perform an updated, comprehensive systematic review of the accuracy of imaging and laboratory tests for the diagnosis of ARS and ABRS.…”
Section: Introductionmentioning
confidence: 99%
“…10,12 The goal of the current study is to perform an updated, comprehensive systematic review of the accuracy of imaging and laboratory tests for the diagnosis of ARS and ABRS.…”
Section: Introductionmentioning
confidence: 99%
“…1 In adults, Gwaltney et al 2 showed extensive radiologic changes in the nasal passages, ostiomeatal area, and sinus cavities during viral colds. It has been assumed that children have similar changes.…”
mentioning
confidence: 99%
“…Entre os pacientes com SAB, a disponibilidade de informação baseada em evidência é menor do que para as situações anteriormente comentadas 59 . Em 2001, a AAP publicou recomendações para o manejo de pacientes com quadro clínico sugestivo de SAB com base em um consenso entre especialistas, de forma a complementar as questões para as quais as evidências eram insuficientes 60 (Figura 4).…”
Section: Uso De Antibióticos Em Infecções De Vias Aéreasunclassified